The Study of Technological Mode Options for Production of Oil of Required Quality; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Dzhalilova S. N. Sofiya Nasibullaevna (2017, 2017)
Title screen